Exploring the interplay of children's expectations of fairness and authority across cultures - Melani, Irene (2015)
Past research on children’s sociomoral reasoning has widely discussed how children exercise the principles of fairness and authority respectively in reasoning about social situations. However, little research has been conducted to study how children’s expectations of fairness may interact with the principle of authority. Fairness is primarily apprehended as the allocation of resources based on equality, merit, or effort invested. Authority principle, on the other hand, involves the perception of a higher-ranked individual who is ascribed with the role of protecting and maintaining the harmony within the group. Studies in infancy have established that children have acquired the expectations of fairness at the age of 15 months old. Similarly at this age, children have developed the perception of social hierarchy to draw dominance relations. The aim of the current paper is to examine how children’s expectations of fairness will interact with the authority principle, when resource distributions are determined by an authority figure. The current paper also explores how culture plays a role in instilling the idea of authority and fairness, through the emphasis of culture-specific values.